A Novel Calcium-Activated Potassium Channel Controls Membrane Potential and Intracellular pH in Trypanosoma cruzi - Barrera, Patricia; Skorka, Christopher; Boktor, Michael; Dave, Noopur; Jimenez, Veronica (Frontiers in Cellular and Infection Microbiology, 2020)
Trypanosoma cruzi develops in environments where nutrient availability, osmolarity, ionic concentrations, and pH undergo significant changes. The ability to adapt and respond to such conditions determines the survival and successful transmission of T. cruzi. Ion channels play fundamental roles in controlling physiological parameters that ensure cell homeostasis by rapidly triggering compensatory mechanisms. Combining molecular, cellular and electrophysiological approaches we have identified and characterized the expression and function of a novel calcium-activated potassium channel (TcCAKC). This channel resides in the plasma membrane of all 3 life stages of T. cruzi and shares structural features with other potassium channels. We expressed TcCAKC in Xenopus laevis oocytes and established its biophysical properties by two-electrode voltage clamp. Oocytes expressing TcCAKC showed a significant increase in inward currents after addition of calcium ionophore ionomycin or thapsigargin. These responses were abolished by EGTA suggesting that TcCAKC activation is dependent of extracellular calcium. This activation causes an increase in current and a negative shift in reversal potential that is blocked by barium. As predicted, a single point mutation in the selectivity filter (Y313A) completely abolished the activity of the channels, confirming its potassium selective nature. We have generated knockout parasites deleting one or both alleles of TcCAKC. These parasite strains showed impaired growth, decreased production of trypomastigotes and slower intracellular replication, pointing to an important role of TcCAKC in regulating infectivity. To understand the cellular mechanisms underlying these phenotypic defects, we used fluorescent probes to evaluate intracellular membrane potential, pH, and intracellular calcium. Epimastigotes lacking the channel had significantly lower cytosolic calcium, hyperpolarization, changes in intracellular pH, and increased rate of proton extrusion. These results are in agreement with previous reports indicating that, in trypanosomatids, membrane potential and intracellular pH maintenance are linked. Our work shows TcCAKC is a novel potassium channel that contributes to homeostatic regulation of important physiological processes in T. cruzi and provides new avenues to explore the potential of ion channels as targets for drug development against protozoan parasites.